Cost-effectiveness of using geotextiles in flexible pavements. Issue 1 (February 2007) - Yang, S.-H.; Al-Qadi, I. L.
Abstract : Using geotextiles in secondary roads to stabilize and reinforce weak subgrades has been a well-accepted practice over the past 30 years. However, from an economics point of view, a complete life-cycle cost analysis, which includes not only costs to agencies but also costs to users of the road, is urgently needed to assess the benefits of using geotextiles in secondary road flexible pavements. This paper presents a cost analysis process that includes costs for the initial construction, each rehabilitation, work-zone queue delays, moving delays, accidents, and fuel consumption. Two of the most practical design methods, developed by Al-Qadi and Perkins, were adopted to quantify the cost–benefits provided by geotextiles when incorporated in secondary road flexible pavements. Although both methods showed significant traffic benefit ratio (TBR) at very low California Bearing Ratio (CBR), the benefits suggested by Perkins diminished as the CBR became greater than 2%. This study also shows that, when user costs are considered, a greater TBR value may not result in the most effective life-cycle cost. Hence, for an optimum secondary road flexible pavement design with geotextile incorporated in the system, a life-cycle cost analysis that includes user cost must be performed.